Roles of dendritic cells in murine hepatic warm and liver transplantation‐induced cold ischemia/reperfusion injury123. Issue 4 (8th April 2013) - Zhang, Matthew; Ueki, Shinya; Kimura, Shoko; Yoshida, Osamu; Castellaneta, Antonino; Ozaki, Kikumi S.; Demetris, Anthony J.; Ross, Mark; Vodovotz, Yoram; Thomson, Angus W.; B. Stolz, Donna; Geller, David A.; et al.
Abstract Dendritic cells (DCs) induce and regulate both innate and adaptive immune responses; however, their in vivo functional importance in hepatic ischemia/reperfusion (IR) injury is perplexing. We hypothesized that liver‐resident DC and locally recruited blood‐borne DC might have distinctive roles in hepatic IR injury. We tested this hypothesis by using DC‐deficient, fms‐like tyrosine kinase 3 ligand (Flt3L) knockout (KO) mice in hepatic warm (70% partial clamping for 60 minutes) and cold IR injury (liver transplant [LTx] with 24‐hour cold storage). Flt3L KO liver and lymphoid organs contained virtually no CD11c+F4/80− DC. Hepatic warm IR injury was significantly lower in Flt3L KO than in wildtype (WT) mice with lower alanine aminotransferase (ALT) levels, reduced hepatic necrosis, and lower neutrophil infiltration. Hepatic messenger RNA (mRNA) and protein levels for inflammatory cytokines (tumor necrosis factor alpha [TNFα], interleukin [IL]‐6) and chemokines (CCL2, CXCL2) were also significantly lower in Flt3L KO than in WT mice, indicating that lack of both liver‐resident and blood‐borne DC ameliorated hepatic warm IR injury. Adoptive transfer of splenic or hepatic WT DC into Flt3L KO or WT mice increased hepatic warm IR injury, suggesting injurious roles of DC infusion. When Flt3L KO liver was transplanted into WT mice, ALT levels were significantly higher than in WT to WT LTx, with enhanced hepatic necrosis and neutrophil infiltration, indicating a protective role of liver‐resident DC. Conclusion: Using both warm and cold hepatic IR models, this study suggests differential roles of liver‐resident versus blood‐borne DC, and points to the importance of the local microenvironment in determining DC function during hepatic IR injury. (HEPATOLOGY 2013;57:1585–1596)